Promotive Role of 5-Aminolevulinic Acid or Salicylic Acid Combined with Citric Acid on Sunflower Growth by Regulating Manganese Absorption - Juanjuan Li; Jianmin Pan; Ullah Najeeb; Hossam S. El-Beltagi; Qian Huang; Huaijian Lu; Ling Xu; Bixian Shi; Weijun Zhou (MDPI AG, 2023)
Manganese (Mn) is an essential nutrient in most organisms. Establishing an effective regulatory system of Mn absorption is important for sustainable crop development. In this study, we selected sunflower as the model plant to explore the effects of 5-aminolevulinic acid (ALA) or salicylic acid (SA) combined with citric acid (CA) on Mn absorption. Six-leaf-old sunflower plants were exposed to 0.8 g kg−1 Mn for one week and then treated with chelating agents, i.e., CA (10 mmol kg−1), and different concentrations of ALA and SA for one week. The results showed that Mn-treated plants had significantly increased H2O2, O2− and MDA contents in leaves compared with the control. Under the Mn + CA treatment, ALA or SA2 significantly activated the antioxidant defense system by increasing SOD, POD and CAT activities in leaves. Moreover, the application of CA significantly increased the Mn uptake in sunflower roots compared with Mn treatment alone; however, did not accelerate the translocation efficiency of Mn from sunflower roots to shoots. Moreover, ultrastructural and RT-qPCR results further demonstrated that ALA/SA could recover the adverse impact of excessive Mn accumulation in sunflowers. Like a pump, ALA/SA regulated the translocation efficiency and promoted the transportation of Mn from roots to shoots. This study provides insights into the promotive role of ALA/SA combined with CA on sunflower growth by regulating Mn absorption, which would be beneficial for regulating Mn absorption in soil with an Mn deficit.